KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI KARAKTERISTIK CARA BERPIKIR PADA MATERI FUNGSI DI MA - Meisari, Hudy; Yusmin, Edy; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out the ability of mathematical representation of students that have characteristics of concrete sequential, abstract sequential, concrete random, and abstract random thinking in grade XI at MA Mathla'ul Anwar Pontianak. This form of quantitative descriptive research, for the data collection techniques used are test techniques and indirect communication techniques. The data collection instrument used are polls and problems with test. It is obtained that students with characteristics different ways of thinking in relatively understand the context of the problem, can present the information provided in visual, verbal and symbol forms. Student with concrete and random sequential thinking types are students having high visual representation abilities, while student with abstract and random sequential thinking have high symbolic and verbal representation abilities. The ability of symbolic representation is the highest ability in every way of thinking students with a high percentage, then the ability of visual and verbal representation has the same percentage in the way of students thinking.Â Keywords: Ability ofÂ Represenasi Matematis, Function, Characteritic way of thinking